2001
DOI: 10.1074/jbc.m011688200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces the Activation of the Phosphatidylinositol 3-Kinase/Akt Cell Survival Pathway in PC12 Cells

Abstract: Hypoxia is a common environmental stress that influences signaling pathways and cell function. Several cell types, including neuroendocrine chromaffin cells, have evolved to sense oxygen levels and initiate specific adaptive responses to hypoxia. Here we report that under hypoxic conditions, rat pheochromocytoma PC12 cells are resistant to apoptosis induced by serum withdrawal and chemotherapy treatment. This effect is also observed after treatment with deferoxamine, a compound that mimics many of the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
169
4
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(193 citation statements)
references
References 34 publications
16
169
4
4
Order By: Relevance
“…[31][32][33] However, in this study, the I/R ratio of the rats exposed to low barometric pressure hypoxia was significantly higher than that of the rats pretreated with 1000 ppm CO. And the activation of MAPKs, Akt, and eNOS induced by hypoxia was significantly weaker than that induced by 1000 ppm CO. In addition, I/R ratio was significantly lower in the rats pretreated with 1000 ppm CO than in those pretreated with 500 ppm CO, although the concentrations of HbCO in blood were not significantly different between the 2 groups (30.1% and 24.9% at 24 hours of inhalation, respectively).…”
Section: Discussioncontrasting
confidence: 44%
“…[31][32][33] However, in this study, the I/R ratio of the rats exposed to low barometric pressure hypoxia was significantly higher than that of the rats pretreated with 1000 ppm CO. And the activation of MAPKs, Akt, and eNOS induced by hypoxia was significantly weaker than that induced by 1000 ppm CO. In addition, I/R ratio was significantly lower in the rats pretreated with 1000 ppm CO than in those pretreated with 500 ppm CO, although the concentrations of HbCO in blood were not significantly different between the 2 groups (30.1% and 24.9% at 24 hours of inhalation, respectively).…”
Section: Discussioncontrasting
confidence: 44%
“…Hif-1a promotes cell death through an increase in p53 or other proapoptotic proteins such as Bcl-2/E1B 19 kDa interacting protein 3 (BNIP3) or BNIP3L (NIX) (Carmeliet et al, 1998;Bruick, 2000;Guo et al, 2001;Sowter et al, 2001). Under most circumstances however, Hif-1a promotes survival of cancer or endothelial cells under hypoxic condition and also protects against apoptosis induced by serum deprivation or by anticancer agents (Alvarez-Tejado, 2001; Sasabe et al, 2005;Piret et al, 2004;Kim et al, 2004a, b;Zhang et al, 2004). Hif-1a exerts its antiapoptotic function by transcriptional activation of antiapoptotic proteins, for example, those of the Bcl-2 family or inhibitor of apoptosis 'IAPs', or by alterations in cellular energy metabolism through increased glucose uptake and glycolysis (Mathupala et al, 2001;Park et al, 2002;Dong et al, 2003;Zhang et al, 2004;Blum et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, virus-driven elevated Akt expression was shown to enhance survival of hydrogen peroxide-treated HeLa and NIH3T3 cells. These findings have been extended to other model systems of oxidative stress including treatment with neurotoxins known to generate ROS and models of oxidative preconditioning (Alvarez-Tejado et al, 2001;Han et al, 2001;Salinas et al, 2001).…”
Section: Pi3-kinase/akt Pathwaymentioning
confidence: 88%